A Study of College English Writing Teaching Based on Dynamic Assessment - SUN, YAJIE (Pacific International Journal, 2023)
For a long time, college-level English writing teaching in China has relied mainly on summative tests, which provide a single and rigid evaluation criteria and limit students' all-around development of writing ability. However, with the current reform of college English teaching, the single assessment method cannot cater to the changing needs of the new teaching model, which emphasizes the cultivation of students' ability to use language. To address this issue, this paper proposes introducing the notion of dynamic assessment into English writing classes at the college level. Dynamic assessment emphasizes the assessment of the learning process and feedback of teaching information, which can lead to a comprehensive, scientific, and reasonable assessment system that plays a crucial role in realizing teaching objectives. Based on Vygotsky's sociocultural theory of mind, this paper presents scaffolding strategies for each stage of writing in college English writing teaching and learning. These strategies serve as a foundation for constructing a theoretical dynamic assessment model in Chinese non-English majors' writing classes. By introducing dynamic assessment into college English writing teaching, this paper aims to explore new methods that increase the efficiency of college English writing teaching and promote college students' English writing ability to adapt to the reform of new requirements for college English teaching.